A flórula fanerogâmica do Estado do Pará. Ilhas de Maiandeua e Algodoal - família dilleniaceae dc. (Museu Paraense Emílio Goeldi, 2022)
In the sandbanks of Algodoal and Maiandeua islands the family Dilleniaceae DC. is represented by the species Doliocarpus spragui Sheesman, Tetracera willdenowiana Stend. and Davilla nitida (Vall.) Kubliana. We used material collected on the islands of Maiandeua and Algodoal and specimens from the MPEG herbarium. Morphological observations were made using a ZEISS stereomicroscope with a clear camera. The nomenclature used to indicate the form and density of the morphological structures was based on the works of LAWRENCE (1973) and RIZINNI (1977). The presence of many sclereids in the epidermis of the leaves of these species gives them a rigid structure with a coriaceous consistency. The species studied are lianas, with inflorescence in bunches, actinomorphic corolla, pentamerous and androids with numerous stamens. Doliocarpus spragui stands out for being glabrous, with larger leaves than the other two species and anther with longitudinal descent. Tetracera willdenoviana is characterized by the crenate margins of its leaves, by their arrangement on the branch and by its poricidal anthers. Davila nitida presents the stem with an apparent shedding, the petiole much more developed than the other two species and anther with longitudinal descent. Studies on the leaf anatomy of the species are being carried out.